2019
DOI: 10.1002/ijc.32376
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of myofibroblast activities in metastasis and fibrosis by methyltransferase inhibition

Abstract: Myofibroblasts are a population of highly contractile fibroblasts that express and require the activity of the transcription factor Snail1. Cancer-associated fibroblasts (CAFs) correlate with low survival of cancer patients when present in the stroma of primary tumors. Remarkably, the presence of myofibroblastic CAFs (which express Snail1) creates mechanical properties in the tumor microenvironment that support metastasis. However, therapeutic blockage of fibroblast activity in patients with cancer is a double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…These two studies highlight the importance of blocking the TGFbeta pathway on CAFs, a pathway that was recently shown to be associated with the immune-suppressive properties of CAFs [44]. In addition, a recent study, described that methyltransferase inhibitors (targeting both histones and DNA methylation), could block the capacity of CAFs to remodel the ECM and prevent metastasis formation in a model of breast cancer, through the interaction of SNAIL with the methyltransferase PRMT1 and PRMT4 [101].…”
Section: -Histone Modifying Enzyme Inhibitorsmentioning
confidence: 90%
“…These two studies highlight the importance of blocking the TGFbeta pathway on CAFs, a pathway that was recently shown to be associated with the immune-suppressive properties of CAFs [44]. In addition, a recent study, described that methyltransferase inhibitors (targeting both histones and DNA methylation), could block the capacity of CAFs to remodel the ECM and prevent metastasis formation in a model of breast cancer, through the interaction of SNAIL with the methyltransferase PRMT1 and PRMT4 [101].…”
Section: -Histone Modifying Enzyme Inhibitorsmentioning
confidence: 90%
“…During inhibition of methylation activity via 5-aza or short interfering RNA (siRNA) specific for DNMT1, DNMT3a, and DNMT3b, α-SMA expression increased, while transfection with plasmids containing DNMT genes did the opposite [48], underlying the importance of these mechanisms in epithelial-mesenchymal transition (EMT) regulation. Other methyltransferase inhibitors such as arginine N-methyltransferase inhibitor-1 (AMI1) and sinefungin also present the potential to disrupt the ECM architecture generated by IPF fibroblasts, as recently discovered by Sala et al [49].…”
Section: Myofibroblast Differentiationmentioning
confidence: 94%
“…There is also evidence that TGF-β1 regulates fibroblast activation by modulating the activity of the transcription factor Snail1. Of note, it was recently reported that TGF-β1/Snail1 enhances the activation of both pulmonary fibroblasts and breast cancer TAFs by cooperating with two protein methyltransferases (PRMT1 and PRMT4) to promote arginine methylation in histones, which drive the expression of fibronectin and other pro-fibrotic genes [65], thereby supporting that histone methylation is involved in fibroblast activation and fibrosis [66]. However, the role of PRMTs in lung TAFs remains unexplored.…”
Section: Histone Core Modifications and Dnmts In Fibroblast Activationmentioning
confidence: 99%
“…On the other hand, following the recent discovery that TGF-β1/Snail1 elicits histone modifications in fibroblast by cooperating with two protein methyltransferases, inhibitors of methyltransferases were tested, including sinefungin and arginine methyltransferase inhibitor 1 (AMI-1) (Table 1), and were found to prevent myofibroblast activity in culture and in vivo, as well as to reduce metastasis in a mouse breast cancer model [65]. These results support that methyltransferase inhibitors hold potential against the tumor-promoting effects of activated TAFs [65]. Similarly, it was reported that treating hepatic stellate cells with the global DNA demethylating agent 5-AZA prevented their activation towards a myofibroblast-like phenotype [119].…”
Section: Drugs That Modify Dna Methylation Marks In Fibroblasts and Mesenchymal Cellsmentioning
confidence: 99%